Qualidade de mangas cv. palmer após armazenamento sob baixas temperaturas - Miguel, Ana Carolina Almeida; Durigan, José Fernando [UNESP]; Barbosa, José Carlos [UNESP]; Morgado, Cristiane Maria Ascari [UNESP] (FapUNIFESP (SciELO), 2013)
This study aimed to evaluate the quality of 'Palmer' mangoes previously stored at low temperatures, after their transference to the environmental condition. Fruits harvested at physiological maturity were carefully transported to the Laboratory where they were selected, standardized as the color, size and absence of injuries and treated with fungicide before they were stored at 2°C (75.7% RH), 5°C (73.8% RH) e 12°C (82% RH) for 7, 14 and 21 days. At the end of each period, the fruits were transferred to environmental condition (22.9°C; 62.3% RH), where they were kept for 1, 3, 5 and 7 days, simulating the trading period, and evaluated for the occurrence of injuries and rottenness; peel and pulp color; firmness; contents of soluble solids, titratable acidity and ascorbic acid, as well as, the activities of the enzymes peroxidase, polyphenoloxidase and phenylalanine ammonia-lyase. The results indicated that 'Palmer' mangoes can be stored at 12°C for 21 days without damage to ripening, but with limitations due to the occurrence of decay. The storage at 2°C and 5°C was limited by the occurrence of injuries in the peel, but at the temperature of 2°C these symptoms were more severe and compromised the development of the characteristic color of the peel. However, the ripening of the pulp was not harmed, but this process occurred with less intensity than in mangoes maintained at 12°C.
Quality of mangoes cv. Palmer after their storage under low temperatures
Keywords: Chilling injury; Conservation; Decay; Enzymes; Mangifera indica